The Value of Being of The Supporting Characters in The Movie “Luca” - Pranata, I Made Yudisthira Adhi; Jayantini, I Gusti Agung Sri Rwa; Winarta, Ida Bagus Gede Nova (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
This study attempts to reveal the moral value based on the classification of Linda and Eyre (1993) in the movie Luca. This study aimed to find out the value of being of the supporting characters in the movie Luca. It utilized a descriptive qualitative method. This study used the theory of moral values proposed by Linda and Eyre (1993) in their book entitled Teaching Your Children Values. The findings showed there were three types of moral values found in the supporting characters in the movie Luca. They are honesty, peaceability, and courage. The moral value of honesty and peaceability dominantly appeared in this movie. It related to their inner sincere and self-control which contributes building the movie as a whole. These data mainly revealed through the process that each characters engaged, along with its related situation in the movie.